Pengembangan Bahan Ajar Bahasa Arab Berbasis Aplikasi Android - Wijaksono, Agung (At-Turost : Journal of Islamic Studies, 2020)
Speaking skills in Arabic or commonly known as maharatul kalam is one of the important language skill, but it is almost very rare for Madrasah Ibtidaiyah students today to have good Arabic speaking skills, this has attracted the attention of researchers to develop teaching material products. what is interesting for students in this case is the teaching materials based on the Android application. The purpose of this development research is to describe the development model, to describe attractiveness and effectiveness and to determine the shape of the product. This research and development method of teaching materials based on the Borg and Gall’s R&D model, that is (1) Research and Information Collecting, (2) Planning, (3) Develop preliminary of product, (4 )Preliminary field testing, (5) Main product revition, (5) Main field testing, (6) Operasional product revision, (7) Operasional field testing, (8) Final product revision, (9) Disseminate, (10) implementation. The results of research and development of this teaching material are in the form of Android application software in apk and swf formats.